Reliability analysis and asset management of engineering systems - Souza, Gilberto Francisco Martha de; Caminada Netto, Adherbal; Melani, Arthur Henrique De Andrade; Michalski, Miguel Angelo De Carvalho; Silva, Renan Favarao da (Advances in reliability science, 2022)
This book fills a gap on how to deal with such complex systems by linking the concepts of systems reliability and asset management, and then making these solutions more accessible to industry by explaining the availability analysis of complex systems based on simulation methods that emphasise Petri nets. --